A complete study on an asphalt concrete modified with graphene and recycled hard-plastics: A case study. (December 2022) - Russo, Francesca; Eskandarsefat, Shahin; Venturini, Loretta; Viscione, Nunzio
Abstract: To date, many asphalt modifiers have been introduced and tested in the road pavement industry aiming at improving the properties of asphalt concrete and consequently its service life. In this context, also considering the environmental and circular economy principles, recently waste plastics, as a source of plastomeric polymers, have gotten more attention. This paper presents a complete case study on an asphalt pavement containing an asphalt concrete modifier composed of recycled hard plastics and graphene nanoplatelets that is compared with its counterpart made of SBS Polymer-modified Bitumen (PmB). The study aimed at providing a complete knowledge on a real-scale job and practical issues using such modifier that has not been well-reported within the current literature. This paper is divided into I) mix design and pre-qualification, 2) post-production tests, and 3) two years of monitoring of the trial section. Based on the results, the mixtures modified with recycled-plastic additives showed higher stiffness and tenacity and as expected though, a higher resistance to permanent deformation in line with the literature. As far as the fatigue is concerned, a similar fatigue endurance was observed for both of the studied asphalt concretes. In addition, the pavement condition survey carried out by pavement experts did not reveal any distress or failure for both of the executed pavements. Highlights: Hot modified asphalt mixtures. Graphene enhanced polymer adopted as asphalt modifier. Mechanical and volumetric characterization of Hot Asphalt Mixtures. Real scale trial testing section.